Characterization of voltage-gated sodium channel subtypes expressed in the human rhabdomyosarcoma cell line TE671 - Muhammad Yusran, Abdul Aziz; Mellor, Ian R; Smith, Paul A (2017)
The TE671 cell line has been widely used as a model of human medulloblastoma1 . Further analysis showed that its phenotypic and cytogenetic properties were similar to the human muscle RD cell line, hence, TE671 was ascribed as rhabdomyosarcoma rather than medulloblastoma2 . Previous studies showed that TE671 cells exhibited voltage-gating properties, cation selectivity and neurotoxin sensitivity-characteristic of ‘classical’ sodium channels of excitable cell2